Finite element analysis of relationship between tightening torque and initial load of bolted connections - Qingmin Yu; Honglei Zhou; Libin Wang (Advances in Mechanical Engineering, 2015)
Proper initial load is necessary to ensure the stability of the bolted connections. In order to apply appropriate torque, the relationship between tightening torque and initial load should be determined. In this study, a detailed three-dimensional finite element model of bolted joints was established with consideration of helix angle, pitch, thread type, tooth-type angle, and other details. The process of pre-tightening of bolted joints was simulated to validate the finite element model. The curves for the relationship between the torque and initial load obtained from finite element analysis agree well with those calculated from theoretical equations. Then, the influence of the friction coefficient, pitch, elastic modulus, assembly clearance, and strain-hardening exponent on the relationship was studied. The results show that the friction coefficient between nut and joint has great influence on the relationship between torque and initial load, that is, the larger the friction coefficient, the smaller the initial load of bolt at the same tightening torque. In contrast, the pitch, assembly clearance, Young’s modulus, and strain-hardening exponent have little influence on torque–initial load relation. The method used in this study provides a theoretical basis for accurately determining the tightening torque for bolted joints.